The impact of the Russian-Ukrainian war on the mental health of Italian people after 2 years of the pandemic: risk and protective factors as moderators - Mottola, Francesca; Gnisci, Augusto; Kalaitzaki, Argyroula; Vintilă, Mona; Sergi, Ida (Frontiers in Psychology, 2023)
This contribution aimed at investigating the moderating role of risk (e.g., the negative influence of COVID-19 on mental health) and protective (e.g., post-traumatic growth) factors on the relationship between the concern for war and stress and anxiety/depression levels among Italian people. A questionnaire that included sociodemographic characteristics, the Perceived Stress Scale (PSS-4), the Patient Health Questionnaire (PHQ-4), the Brief Resilience Scale (BRS), the Post-Traumatic Growth Inventory (PTGI), and questions formulated ad hoc about concern for war was administered online. A sample of 755 participants (65.4% females, mean age = 32.39, SD = 12.64, range = 18-75) was recruited by convenience and snowball sampling. The researchers spread the link to the questionnaire to their acquaintances asking them to fill it out and to recruit other people. Results showed that concern for war significantly augmented the levels of stress and anxiety/depression in Italian people. Being a healthcare professional or having a chronic illness negatively moderated the effect of concern for war on stress and anxiety/depression. Instead, the negative influence of COVID-19 on mental health positively moderated the effect of concern for war on stress. Moreover, the overall positive changes after trauma and four of its five scales (i.e., Relating to Others, New Possibilities, Personal Strength, and Spiritual Change), negatively moderated the effect of concern for war on anxiety/depression. In conclusion, concern about the Russian-Ukrainian war affects the mental health of the Italian population even if they are not directly involved in the conflict.